Creative Industries and Cultural Tourism: A Bibliometric Perspective on Art, Design, and Heritage Travel - Judijanto, Loso; Latif, Latif; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study explores the evolving intersection between creative industries and cultural tourism through a comprehensive bibliometric analysis, with particular emphasis on themes such as art, design, and heritage travel. Drawing on publication data from the Scopus database between 2000 and 2025, the research employs VOSviewer to analyze keyword co-occurrence, author co-citation, and country collaboration networks. The findings reveal tourism as the central thematic hub, closely linked with concepts like sustainable development, creative economy, and innovation. Emerging keywords such as augmented reality, product design, and user experience suggest a growing scholarly interest in integrating digital technologies into cultural tourism experiences. Influential scholars including Richards, Florida, and Duxbury are identified as shaping the intellectual core of the field, while regional trends point to the increasing prominence of contributions from China, Indonesia, and other Southeast Asian nations. This study highlights the multidisciplinary nature of the discourse and identifies research gaps in technological innovation and cross-regional collaboration. It concludes by emphasizing the potential of creative industries to drive sustainable and participatory tourism development in the post-pandemic era.